Effects of chronic secondhand smoke exposure on cardiovascular regulation and the role of soluble epoxide hydrolase in mice - Pan, Shiyue; Karey, Emma; Nieves-Cintron, Madeline; Chen, Yi-Je; Hwang, Sung Hee; Hammock, Bruce D.; Pinkerton, Kent E.; Chen, Chao-Yin (Frontiers in Physiology, 2023)
Background: Secondhand smoke (SHS) is a significant risk factor for cardiovascular morbidity and mortality with an estimated 80% of SHS-related deaths attributed to cardiovascular causes. Public health measures and smoking bans have been successful both in reducing SHS exposure and improving cardiovascular outcomes in non-smokers. Soluble epoxide hydrolase (sEH) inhibitors have been shown to attenuate tobacco exposure-induced lung inflammatory responses, making them a promising target for mitigating SHS exposure-induced cardiovascular outcomes. Objectives: The objectives of this study were to determine 1) effects of environmentally relevant SHS exposure on cardiac autonomic function and blood pressure (BP) regulation and 2) whether prophylactic administration of an sEH inhibitor (TPPU) can reduce the adverse cardiovascular effects of SHS exposure. Methods: Male C57BL/6J mice (11 weeks old) implanted with BP/electrocardiogram (ECG) telemetry devices were exposed to filtered air or 3 mg/m3 of SHS (6 hr/d, 5 d/wk) for 12 weeks, followed by 4 weeks of recovery in filtered air. Some mice received TPPU in drinking water (15 mg/l) throughout SHS exposure. BP, heart rate (HR), HR variability (HRV), baroreflex sensitivity (BRS), and BP variability were determined monthly. Results: SHS exposure significantly decreased 1) short-term HRV by ~20% (p<0.05) within four weeks; 2) overall HRV with maximum effect at 12 weeks (-15%, p<0.05); 3) pulse pressure (-8%, p<0.05) as early as week 4; and 4) BRS with maximum effect at 12 weeks (-11%, p<0.05). Four weeks of recovery following 12 weeks of SHS ameliorated all SHS-induced cardiovascular detriments. Importantly, mice exposed to TPPU in drinking water during SHS exposure were protected from SHS cardiovascular consequences. Discussion: These data suggest 1) environmentally relevant SHS exposure significantly reduces cardiac autonomic function and BP regulation; 2) cardiovascular consequences from SHS can be reversed by discontinuing SHS exposure; and 3) inhibiting sEH can prevent SHS-induced cardiovascular dysregulation.